2011
DOI: 10.1021/jf200988f
|View full text |Cite
|
Sign up to set email alerts
|

Potato Extract (Potein) Suppresses Food Intake in Rats through Inhibition of Luminal Trypsin Activity and Direct Stimulation of Cholecystokinin Secretion from Enteroendocrine Cells

Abstract: Dietary proteins and trypsin inhibitors are known to stimulate the secretion of the satiety hormone cholecystokinin (CCK). A potato extract (Potein) contains 60% carbohydrate and 20% protein including trypsin inhibitory proteins. In this study, we examined whether Potein suppresses food intake in rats and whether it directly stimulates CCK secretion in enteroendocrine cells. In fasted rats, food consumption was measured up to 6 h after the oral administration of Potein or soybean trypsin inhibitor (SBTI). CCK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 35 publications
3
34
1
2
Order By: Relevance
“…5), consistent with the findings in a recent report. 22) The potato extract included proteins other than trypsin inhibitors and other non-protein components, so some of these components might be responsible for the direct stimulation of CCK secretion. It is likely that CCK secretion is the result of both the direct action of an active compound on CCK-producing cells and luminal protease inhibition in vivo.…”
Section: Comparison Of Preloading Various Protein and Potatomentioning
confidence: 99%
See 2 more Smart Citations
“…5), consistent with the findings in a recent report. 22) The potato extract included proteins other than trypsin inhibitors and other non-protein components, so some of these components might be responsible for the direct stimulation of CCK secretion. It is likely that CCK secretion is the result of both the direct action of an active compound on CCK-producing cells and luminal protease inhibition in vivo.…”
Section: Comparison Of Preloading Various Protein and Potatomentioning
confidence: 99%
“…Our previous study has shown that in vitro digestion by pepsin and/or pancreatin enhanced the effect of the potato extract on CCK secretion in STC-1 cells, suggesting that peptides from the potato extract liberated by the luminal digestion were responsible for stimulating this CCK release. 22) Further studies are necessary to identify the active components of the potato extract that directly induce CCK secretion and the molecular mechanisms involved in this process.…”
Section: Comparison Of Preloading Various Protein and Potatomentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also demonstrated that trypsin inhibitors can inhibit human neutrophil elastase (HNE) and reduce inflammatory cytokines [16,17,18,19]. Furthermore, trypsin inhibitors increase cholecystokinin (CCK), a satietogenic hormone, which may be the link to reduced food intake and weight loss seen in studies using seeds rich in trypsin inhibitors [15,18,20,21,22]. These studies found that trypsin inhibitors act as CCK inducers, confirming the peripheral and central action of these inhibitors in satiety [23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…37 Para a nutrição, diferente do estigma que os relacionam aos efeitos antinutricionais, esses inibidores possuem papel heterólogo e bioativo no processo de digestão de proteínas, apresentando efeito no controle da saciedade com consequente redução de peso em modelo experimental, tendo em vista que, a partir da diminuição da atividade de tripsina livre e consequente redução da quebra de proteínas e peptídeos, há elevação da concentração do hormônio sacietogênico CCK. 21,22,[38][39][40][41][42] A detecção da atividade antitríptica e o isolamento de um inibidor de tripsina em sementes de chia são achados inéditos, uma vez que não foi encontrado, na busca da literatura científica realizada nas bases de dados, estudos anteriores que tenham analisado a presença desses inibidores. As proteínas da chia têm sido avaliadas quanto possíveis atividades biológicas, 43,44 sendo relatada inclusive a presença de peptídeos com ação inibitória sobre a enzima conversora de angiotensina.…”
Section: Figuraunclassified